Developing “CH-CD Electrolyte Solution Test Tools” Game for Teaching Spoken Procedure Text to Twelfth Graders of Senior High School - Setyawati, Erna (Institut Agama Islam Negeri Kudus, 2018)
The objectives of this research were to develop “CH-CD Electrolyte Solution Test Tools” Game for Teaching Spoken Procedure Text to Twelfth Graders of Senior High School. The subjects of this research were XII MIPA 2 and XII MIPA 6 SMAN 11 Semarang students in the academic year of 2016/2017.The process of this research was conducted in seven stages. The data were analyzed by using qualitative and quantitatives methods. The researcher used t-test formula to analyze the data. Principally, the object of R&D is managing and developing the effectiveness of product applied at schools. The researcher gives the name of this game by own words, it is “CH-CD Electrolyte Solution Test Tools” game.The result of the research shows that “CH-CD Electrolyte Solution Test Tools” game can develop students’ speaking ability. This successfulness can be seen from the result of increasing students’ average score and good responses by studentsafter practising“CH-CD Electrolyte Solution Test Tools” game. The result of the research can be concluded that by using “CH-CD Electrolyte Solution Test Tools” game in teaching spoken procedure text, teacher can improve students’ ability in speaking. And it is hoped that it can be valuable as the information resource for all people.